Pengaruh Penggunaan Media Komik Terhadap Kemampuan Menulis Kalimat Pada Kelas III SD Inpres 15 Kabupaten Sorong - Isir, Fransiska; Faizin, Muhammad; Saputro, Isnaini Eddy (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Learning media is one of the tools used to achieve learning. It is kind of visual or audio. Learning media is easy to understand the material from teacher’s explanation. This research is quantitative method with pre-experimental design. The sample of this research is the third students and the total number is 20 students. To analyse the data is used SPSS application to calculate the result of pre-test and post-test. Based on the result, the average of post-test score is 87.30 with the standard deviation 4.74 and the average of pre-test score is 72.75 with standard deviation 6.27. It means that those scores are calculated statistically to get the score of ttable 0.10 and the significant of paired samples test is 0.00 < 0.05, it indicates that there is an improvement of experimental class that uses comic media in writing sentence. The use of comic media can help the student in writing sentence and students motivate in learning process.